Clinical validation of a novel automated cell‐free DNA screening assay for trisomies 21, 13, and 18 in maternal plasma. (19th August 2019) - Ericsson, Olle; Ahola, Tarja; Dahl, Fredrik; Karlsson, Filip; Persson, Fredrik; Karlberg, Olof; Roos, Fredrik; Alftrén, Ida; Andersson, Björn; Barkenäs, Emelie; Boghos, Ani; Brandner, Birgit; et al.
Abstract: Objective: To evaluate clinical performance of a new automated cell‐free (cf)DNA assay in maternal plasma screening for trisomies 21, 18, and 13, and to determine fetal sex. Method: Maternal plasma samples from 1200 singleton pregnancies were analyzed with a new non–sequencing cfDNA method, which is based on imaging and counting specific chromosome targets. Reference outcomes were determined by either cytogenetic testing, of amniotic fluid or chorionic villi, or clinical examination of neonates. Results: The samples examined included 158 fetal aneuploidies. Sensitivity was 100% (112/112) for trisomy 21, 89% (32/36) for trisomy 18, and 100% (10/10) for trisomy 13. The respective specificities were 100%, 99.5%, and 99.9%. There were five first pass failures (0.4%), all in unaffected pregnancies. Sex classification was performed on 979 of the samples and 99.6% (975/979) provided a concordant result. Conclusion: The new automated cfDNA assay has high sensitivity and specificity for trisomies 21, 18, and 13 and accurate classification of fetal sex, while maintaining a low failure rate. The study demonstrated that cfDNA testing can be simplified and automated to reduce cost and thereby enabling wider population‐based screening. Abstract : What is already known about this topic? Maternal plasma cell‐free (cf)DNA analysis with next-generation sequencing has a high sensitivity and specificity for fetal trisomy 21 and other common autosomal trisomies. A new amplification-free, nonsequencing, and targeted cfDNA assay has been developed. Proof‐of‐principle analysis found the new assay has promising results in screening for trisomy 21. What does this study add? The new assay has high sensitivity and specificity for trisomies 21, 18, and 13 in singleton pregnancies. It can accurately determine fetal sex. It is suitable for use in biochemical screening laboratories since it is highly automated and does not require specialized personnel.